PENERAPAN SISTEM PEMBUKTIAN TERBALIK DALAM UPAYA PEMBERANTASAN TINDAK PIDANA KORUPSI - Sari Merta Dewi, Ayu Komang; Puspawati, I Gusti Ayu (Kertha Negara : Journal Ilmu Hukum, 2013)
Corruption is an extraordinary crime that require exceptional legal instrumentto combat its existence anyway. Of proof systems are specific rules established by thegovernment through the issuance of the provisions of Act No. 31 of 1999 which, asamended in Act No. 20 of 2001 on Eradication of Corruption. Because of the system ofproof applied in criminal acts of corruption is different from the one employed in theprocedural law in general, this paper will explain how the application system in theprocess of evidence of proof at court. In addition, this paper also explains howsystematically the role of proof against the imposition of the ruling by Judge.
Keywords: Reversal Burden Of Proof, Corruption , Eradication